1972
DOI: 10.1128/iai.6.5.852-859.1972
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Distribution and Relative Adherence of Streptococcus miteor ( mitis ) on Various Surfaces in the Human Oral Cavity

Abstract: A group of streptococci possessing the characteristics of Streptococcus miteor (S. mitis) was found to predominate on nonkeratinized human oral mucosa. These organisms averaged from 76 to 89%C of the total flora cultivable on anaerobically incubated blood agar plates from cheek, lip, and ventral tongue surfaces. They averaged 34, 40, and 18%tof the streptococci in dental plaque, in saliva, and on the tongue dorsum, respectively. Their ability to adhere to oral surfaces was studied by introducing mixtures of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 17 publications
2
61
2
Order By: Relevance
“…However, several recent studies have shown that this is not true. 116,117,77,76,118 Differences in bacterial composition between "mature" plaque and saliva have been recognized for many years, 66,37 but these were considered to be due to differences in growth rates between the various bacterial species after they arrived on the tooth surface. For example, S.salivarius, which is present in high proportions on the tongue and in saliva, but only in low proportions on teeth ( Table 1), was presumed to grow only slowly or not at all on the tooth surface.…”
Section: Past Theories Of Plaque Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several recent studies have shown that this is not true. 116,117,77,76,118 Differences in bacterial composition between "mature" plaque and saliva have been recognized for many years, 66,37 but these were considered to be due to differences in growth rates between the various bacterial species after they arrived on the tooth surface. For example, S.salivarius, which is present in high proportions on the tongue and in saliva, but only in low proportions on teeth ( Table 1), was presumed to grow only slowly or not at all on the tooth surface.…”
Section: Past Theories Of Plaque Formationmentioning
confidence: 99%
“…For example, certain bacterial species have been found to adsorb to human enamel powder or teeth in vivo to a greater extent than others. 50,116,117,77,76,118 If the enamel powder is exposed to saliva in vitro to form a film of selectively adsorbed salivary constituents mimicking the natural enamel pellicle, the adsorption of some bacterial species is enhanced while that of other organisms is either unaffected or reduced. This adsorbed salivary layer has been found to increase the adsorption of strains of S.sanguis and S.mitis whereas the adsorption of S.salivarius or S.mutans tends to be unaffected or reduced.…”
Section: Plaque Initiation the Interaction Of Bacteria And The Toothmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by electronmicroscopy of oral streptococci which adhere to buccal epithelial cells in rats has revealed fuzzy coats on the bacteria (Liljemark & Gibbons 1972). These coats are removed by trypsin.…”
Section: Microbial Colonizationmentioning
confidence: 99%
“…PneumoniaCheck TM (ARC Medical Inc.) is a new device designed to collect specimens from the lower respiratory tract exhaled with coughs; in particular, it retains aerosol particles in a dedicated filter, preventing contamination from the upper respiratory tract (figure 1). The filter is then analysed through molecular and microbiological tests, in order to detect the presence of different pathogens [27]. Fluid mechanics principles allow the filter to separate aerosol particles from the lungs and the air coming from the upper respiratory tract.…”
Section: Introductionmentioning
confidence: 99%